(Table 2) Consolidation characteristics of ODP Hole 126-790A samples - Dadey, Kathleen A; Klaus, Adam (Supplement to: Dadey, KA; Klaus, A (1992): Physical properties of volcaniclastic sediments in the Izu-Bonin Area. In: Taylor, B; Fujioka, K; et al. (eds.), Proceedings of the Ocean Drilling Program, Scientific Results, College Station, TX (Ocean Drilling Program), 126, 543-550, https://doi.org/10.2973/odp.proc.sr.126.156.1992, 1992)
We examine the physical properties of volcaniclastic sediments in the forearc and backarc of the Izu-Bonin arc region. Based on our analyses of these and other deposits in the area, we conclude that, with the possible exception of pumice-rich material, unlithified volcaniclastics behave much like detrital deep-sea sediments. In contrast, lithified volcaniclastic sediments display unique physical properties, such as higher electrical resistivity and velocity than expected from porosity values. The primary cause of these phenomena is a lack of interconnectedness of the pore spaces and cementation of the volcaniclastic particles.